INTEGRASI AGILE DAN DESIGN THINKING UNTUK PENINGKATAN EFEKTIVITAS PENGEMBANGAN APLIKASI PENCEGAHAN STUNTING: INTEGRATION OF AGILE AND DESIGN THINKING TO IMPROVE THE EFFECTIVENESS OF STUNTING PREVENTION APPLICATION DEVELOPMENT - Syafira Putri Yuanita; Erba Lutfina; Galuh Wilujeng Saraswati; Resha Meiranadi Caturkusuma (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The prevalence of stunting in Ngasem District, Kediri, poses a significant challenge, with one of the inhibiting factors being the conventional and unengaging educational methods for health cadres. This condition results in low material mastery by cadres and minimal community participation. To address these issues, this study aims to design and implement the SIGAP (Sistem Informasi Gizi Anak dan Pencegahan Stunting / Child Nutrition and Stunting Prevention Information System) mobile application by integrating Agile and Design Thinking methodologies. This approach incorporates the Empathize, Define, and Ideate stages of Design Thinking into the Agile framework to ensure a profound understanding of user needs. The application was developed using Flutter, and its Usability was tested on 25 health cadres in Ngasem District as the primary respondents using the System Usability Scale (SUS) method. The test results showed that the SIGAP application obtained an average SUS score of 90.0. This score classifies the application's Usability into the "Excellent" (A) category, proving that the integration of both methods successfully created an educational platform that is highly usable, interactive, and effective. Broadly, this study contributes as a reference model for the digitalization of public health services and enriches the literature regarding the effectiveness of the hybrid Agile-Design Thinking approach in social technology development.